Main areas of the work of «third sector» organizations under the conditions of the martial law - Vitkovska, Inna (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2022)
<span dir="ltr" style="left: calc(var(–scale-factor)*92.06px); top: calc(var(–scale-factor)*284.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.883032);" role="presentation">The article is devoted to the analysis of the main areas of work of «<span dir="ltr" style="left: calc(var(–scale-factor)*362.35px); top: calc(var(–scale-factor)*284.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.877736);" role="presentation">third sector» <span dir="ltr" style="left: calc(var(–scale-factor)*415.27px); top: calc(var(–scale-factor)*284.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.89962);" role="presentation">organizations in the conditions <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*295.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.905531);" role="presentation">of martial law in Ukraine and the determination of the problems they face in th<span dir="ltr" style="left: calc(var(–scale-factor)*371.95px); top: calc(var(–scale-factor)*295.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.920038);" role="presentation">eir activities. <span dir="ltr" style="left: calc(var(–scale-factor)*92.06px); top: calc(var(–scale-factor)*307.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.922712);" role="presentation">Based on the secondary analysis of statistical data, it was found that the number of non-governmental and <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*318.65px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.950848);" role="presentation">charitable organizations in Ukraine is growing year by year, which is one of the signs of the development of civil <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*330.17px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.894406);" role="presentation">society. During 2022, 96,500 non-governmental and 19,112 charitable organizations were registered in Ukraine. <span dir="ltr" style="left: calc(var(–scale-factor)*92.06px); top: calc(var(–scale-factor)*341.57px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.929736);" role="presentation">The author’s analysis of the websites of non-governmental and charitable organizations and the results of <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*353.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.919342);" role="presentation">sociological research allowed us to conclude that the main trends and areas of work of «<span dir="ltr" style="left: calc(var(–scale-factor)*429.19px); top: calc(var(–scale-factor)*353.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.903426);" role="presentation">third sector» <span dir="ltr" style="left: calc(var(–scale-factor)*484.78px); top: calc(var(–scale-factor)*353.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.883917);" role="presentation">organizations <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*364.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.911315);" role="presentation">include: an increase in the number of non-<span dir="ltr" style="left: calc(var(–scale-factor)*230.33px); top: calc(var(–scale-factor)*364.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.904708);" role="presentation">governmental, charitable organizations, fundraising platforms and volunteer <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*376.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.902695);" role="presentation">headquarters, which are focused on helping the army, internally displaced persons<span dir="ltr" style="left: calc(var(–scale-factor)*395.59px); top: calc(var(–scale-factor)*376.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.881117);" role="presentation">, centers for displaced persons and <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*387.65px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.883621);" role="presentation">victims of war, payment of monetary aid and assistance with evacuation to safe places in Ukraine or abroad; increase in <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*399.17px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.926876);" role="presentation">financing of non-<span dir="ltr" style="left: calc(var(–scale-factor)*127.82px); top: calc(var(–scale-factor)*399.17px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.90971);" role="presentation">governmental and charitable organizations at the expense of international donor org<span dir="ltr" style="left: calc(var(–scale-factor)*471.94px); top: calc(var(–scale-factor)*399.17px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.878513);" role="presentation">anizations; mass <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*410.57px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.896198);" role="presentation">spread of voluntary and charitable practices among the population of Ukraine and the growth of trust in the activities of «<span dir="ltr" style="left: calc(var(–scale-factor)*61.44px); top: calc(var(–scale-factor)*422.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.87986);" role="presentation">third sector» <span dir="ltr" style="left: calc(var(–scale-factor)*114.26px); top: calc(var(–scale-factor)*422.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.883511);" role="presentation">organizations. <span dir="ltr" style="left: calc(var(–scale-factor)*92.06px); top: calc(var(–scale-factor)*433.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.893369);" role="presentation">Based on the analysis of in-depth interviews with the heads of non-governmental and charitable organizations <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*445.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.900803);" role="presentation">of the Kharkiv, Sumy, Poltava and Donetsk regions, which were conducted within the framework of the research topic <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*456.65px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.917241);" role="presentation">of the Sociology of Management and Social Work Department «<span dir="ltr" style="left: calc(var(–scale-factor)*317.57px); top: calc(var(–scale-factor)*456.65px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.886609);" role="presentation">Actual trends in the management of social services» <span dir="ltr" style="left: calc(var(–scale-factor)*530.86px); top: calc(var(–scale-factor)*456.65px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.03318);" role="presentation">in <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*468.19px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.951975);" role="presentation">Novem<span dir="ltr" style="left: calc(var(–scale-factor)*85.94px); top: calc(var(–scale-factor)*468.19px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.909916);" role="presentation">ber 2022, we can to conclude that the most urgent problems of these organizations in the conditions of martial <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*479.59px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.902405);" role="presentation">law are continuation of military operations; creation of safe working conditions for employees and beneficiaries during <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*491.11px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.896821);" role="presentation">air alarms; property dama<span dir="ltr" style="left: calc(var(–scale-factor)*160.34px); top: calc(var(–scale-factor)*491.11px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.882024);" role="presentation">ge; personnel turnover; lack of a sufficient number of specialists and a long search for narrow <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*502.63px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.881999);" role="presentation">specialists (lawyer, psychologist, social worker, crisis consultant); excessive load on one employee; many <span dir="ltr" style="left: calc(var(–scale-factor)*484.78px); top: calc(var(–scale-factor)*502.63px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.882282);" role="presentation">beneficiaries; <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*514.15px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.997679);" role="presentation">a long wait for the collection of fund<span dir="ltr" style="left: calc(var(–scale-factor)*219.77px); top: calc(var(–scale-factor)*514.15px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.964702);" role="presentation">s from donors for the implementation of aid programs; absence of a state <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*525.67px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.947398);" role="presentation">component in the financing of the organization’s projects and the social order for social services provided by the <span dir="ltr" style="left: calc(var(–scale-factor)*56.64px); top: calc(var(–scale-factor)*537.07px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.900906);" role="presentation">organization; lack of technical equipment, etc.